(untitled) (Iraqi Journal of Medical Sciences, 2025)
Background: Polycyclic aromatic hydrocarbons are environmental pollutants prevalent in oil fields. This study examines their impact on human health in Basra. Objective: To assess polycyclic aromatic hydrocarbon levels in individuals exposed to oil fields and their correlation with serum glutathione (GSH) levels. Methods: A case-control study conducted from 15 January to 8 May 2024 involved 120 males aged 25 to 40 years. Group 1 consisted of 40 workers from Al-Rumaila field, Group 2 included 40 from West Qurna field, and Group 3 included 40 controls from the city center. Results: Group 2 had lower polycyclic aromatic hydrocarbon levels than Group 1, while Group 3 had none. GSH levels were significantly lower in Groups 1 and 2 compared to Group 3. Workers with over 10 years of exposure had higher polycyclic aromatic hydrocarbon levels and lower GSH. Conclusion: Polycyclic aromatic hydrocarbons significantly reduce GSH levels, posing health risks. Keywords: Environmental pollutants, glutathione, polycyclic aromatic hydrocarbons. Citation: Abdul-Khaleq MA, Abass HA, Al-Wasiti EA. Polycyclic aromatic hydrocarbons and glutathione levels in basra oil company workers (2024). Iraqi JMS. 2025; 23(1): 177-183. doi: 10.22578/IJMS.23.1.21